2001
DOI: 10.1086/317638
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Human Papillomavirus (HPV) Type 16 DNA Detection by Polymerase Chain Reaction and Its Association with Acquisition and Persistence of Other HPV Types

Abstract: Human papillomavirus (HPV)-16 causes about half the cases of cervical cancer worldwide and is the focus of HPV vaccine development efforts. Systematic data are lacking as to whether the prevention of HPV-16 could affect the equilibrium of infection with other HPV types and thus alter the predicted impact of vaccination on the occurrence of cervical neoplasia. Therefore, the associations of HPV-16 detection with subsequent acquisition of other HPV types and with the persistence of concomitantly detected HPV typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
171
3
10

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(204 citation statements)
references
References 15 publications
20
171
3
10
Order By: Relevance
“…2); but its impact with regard to the percentage of cases theoretically prevented would be higher in Asia (73.5%) and A vaccine that included the 7 most common HPV types shown in Figure 2 (16, 18, 45, 31, 33, 52 and 58) would prevent 87.4% of cervical cancers worldwide: 90.6% in northern Africa, 88.8% in south Asia, 86.5% in sub-Saharan Africa, 85.8% in Europe/North America and 84.9% in Central/South America (data not shown). These estimates assume that the prevention of HPV-16 and HPV-18 infections is unlikely to increase the risk of persistent infection by other HPV types, as has been suggested by Liaw et al 27 Another approach would be to consider that the vaccine is effective for cervical cancer cases linked to multiple types when all the types are included in the vaccine. Under this assumption, the global percent prevention would decrease from 71% to 68.3% for an HPV-16/-18 vaccine and from 87.4% to 85.8% if the 7 most common HPV types were included.…”
Section: Discussionmentioning
confidence: 99%
“…2); but its impact with regard to the percentage of cases theoretically prevented would be higher in Asia (73.5%) and A vaccine that included the 7 most common HPV types shown in Figure 2 (16, 18, 45, 31, 33, 52 and 58) would prevent 87.4% of cervical cancers worldwide: 90.6% in northern Africa, 88.8% in south Asia, 86.5% in sub-Saharan Africa, 85.8% in Europe/North America and 84.9% in Central/South America (data not shown). These estimates assume that the prevention of HPV-16 and HPV-18 infections is unlikely to increase the risk of persistent infection by other HPV types, as has been suggested by Liaw et al 27 Another approach would be to consider that the vaccine is effective for cervical cancer cases linked to multiple types when all the types are included in the vaccine. Under this assumption, the global percent prevention would decrease from 71% to 68.3% for an HPV-16/-18 vaccine and from 87.4% to 85.8% if the 7 most common HPV types were included.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liaw et al 44 observed a reduced risk for subsequent acquisition of a new infection within the same phylogenetic clade A9 in initially cytological normal women, which implies a potential protective cross reactivity within clade A9. The immunologic situation, however, is probably different in cancer patients and cross-reactivity was possibly lost in our group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Low-level cell-mediated cross-reactivity between genetically related HPV types may occur because of the different (not so conformation dependent) nature of the epitopes [57]. Cross-reactive cell-mediated immunity could potentially keep the oncogenic non-vaccine types under control due to naturally occurring boosting by the benign non-vaccine included types [26].…”
Section: Effectiveness Of Vaccination In Prevention Of Cervical Cancementioning
confidence: 99%